2022
DOI: 10.1155/2022/6368311
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10-Modified Adipose-Derived Mesenchymal Stem Cells Prevent Hypertrophic Scar Formation via Regulating the Biological Characteristics of Fibroblasts and Inflammation

Abstract: Hypertrophic scar causes serious functional and cosmetic problem, but no treatment method is known to achieve a satisfactory therapeutic effect. However, mesenchymal stem cells show a possible cure prospect. Here, we investigated the effect of interleukin-10-modified adipose-derived mesenchymal stem cells (IL-10-ADMSC) on the formation of hypertrophic scar. In vitro, IL-10-ADMSC could highly express IL-10 and exhibited stronger inhibition of hypertrophic scar fibroblasts (HSFs) proliferation, migration, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…IL-10-gene-modified AMM cells show increased regenerative wound healing through multiple biological effects, such as enhancing angiogenesis, modulating inflammation, and regulating extracellular matrix remodeling [ 18 ]. In addition, IL-10-modified adipose MSCs prevent hypertrophic scar formation by regulating inflammation [ 19 ]. In line with these reports, our results showed that secretory factors derived from AMM/CI regulated phagocytosis and anti-inflammation in macrophages, indicating favorable effects on wound healing via the regulation of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10-gene-modified AMM cells show increased regenerative wound healing through multiple biological effects, such as enhancing angiogenesis, modulating inflammation, and regulating extracellular matrix remodeling [ 18 ]. In addition, IL-10-modified adipose MSCs prevent hypertrophic scar formation by regulating inflammation [ 19 ]. In line with these reports, our results showed that secretory factors derived from AMM/CI regulated phagocytosis and anti-inflammation in macrophages, indicating favorable effects on wound healing via the regulation of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 The administration of anti‐inflammatory treatments to wounded tissues at an early time point has the potential to protect against scar formation while driving more rapid healing responses, with cytokines serving as central regulators of HS‐related inflammation. 7 , 9 , 10 , 11 , 12 Here, TNF‐α, IL‐1β, and IL‐6 expression levels were found to be significantly elevated in HSFs under basal conditions, while TSG‐6 treatment suppressed the expression of all three of these cytokines, in line with prior evidence from a rabbit ear HS model system in which TSG‐6 was able to prevent scar formation in part via suppressing IL‐1β, IL‐6, and TNF‐α expression. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 33 NF‐κB (p65) serves as a core transcriptional regulator of inflammation‐related gene expression, 34 , 35 with growing evidence suggesting that NF‐κB activation can promote pro‐inflammatory gene expression, thereby triggering inflammatory cascades that drive HS development. 9 , 11 , 12 Furthermore, NF‐κB acts as an important link between ER stress and inflammatory response. 15 , 33 While ER stress can thus induce IRE1α‐mediated inflammatory NF‐κB signalling, no prior studies have reported on the link between this signalling axis and HS formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations